Patterns, risk factors, and mental health correlates of cyber intimate partner violence in Hispanic emerging adults - Cano-Gonzalez, Ines (Journal of family violence, 2023)
Purpose: Technology and social media provide new opportunities to commit violence against an intimate partner (IPV). The present study aimed to investigate the patterns of exposure to cyber IPV perpetration and victimization types, related risk factors (i.e., adverse experiences during childhood) and mental health correlates among Hispanic emerging adults. Method: A three-step latent class analysis was performed in a sample of 1,113 Hispanic emerging adults in the age range 18 to 29 years (M = 20.53 years, SD = 2.47). Results: A five-class solution was found to be optimal, and the latent classes were labeled as low cyber, cyberstalking IPV, cyber psychological IPV, cyberstalking and psychological IPV, and high cyber IPV victimization and perpetration. Individuals with higher mean scores on childhood maltreatment and witnessing parental violence were more likely to be in the class with higher probabilities of cyber IPV victimization and perpetration. Furthermore, those in the cyber IPV victimization and perpetration class had higher means on symptoms of depression and alcohol use. Conclusions: Latent classes showed bidirectional cyber IPV with varying probabilities of exposure to victimization and perpetration. Findings are in line with the cumulative risk hypothesis as results showed that exposure to multiple traumatic childhood experiences and cyber IPV accumulate and have a detrimental effect on the mental health correlates. Intervention and preventative strategies should address the impact of hazardous use of technology on intimate relationships and mental health correlates.